First Record of Spintherophyta aurichalcea (Germar, 1824) (Coleoptera: Chrysomelidae) Damaging Ilex paraguariensis (St. Hil.) Crops in Argentina - Schapovaloff, Maria Elena; Scherf, Abel Nicolás; Costa, Marcos Rubén; Gramajo, Maria Cecilia; Ohashi, Diana Virginia; Ayala, Daniela Sofia (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2026)
Ilex paraguariensis (St. Hil.), commonly known as yerba mate, is a native plant to South America and cultivated in Argentina, Brazil and Paraguay. In Argentina, yerba mate is produced and cultivated throughout the province of Misiones and northeastern Corrientes. Yerba mate is a major crop in this region, providing raw material for beverages and active compounds for the pharmaceutical industry. Yerba mate crops are attacked by different phytophagous insects that can cause significant damage. This study reports the first confirmed record of Spintherophyta aurichalcea (Germar, 1824) as a phytophagous insect damaging commercial Ilex paraguariensis plantations in Misiones and Corrientes provinces, Argentina. Highligths: First confirmed record of Spintherophyta aurichalcea damaging Ilex paraguariensis crops in Argentina. The beetle was detected in commercial yerba mate plantations in Misiones and Corrientes provinces. Adults feed on young shoots and mature leaves, causing necrotic and perforated damage. Findings provide baseline information for future monitoring and pest management strategies.